Ablation of Osteopontin Improves the Skeletal Phenotype of Phospho1−/− Mice. (November 2014) - Yadav, Manisha C; Huesa, Carmen; Narisawa, Sonoko; Hoylaerts, Marc F; Moreau, Alain; Farquharson, Colin; Millán, José Luis
ABSTRACT PHOSPHO1 and tissue‐nonspecific alkaline phosphatase (TNAP) have nonredundant functions during skeletal mineralization. Although TNAP deficiency (Alpl−/− mice) leads to hypophosphatasia, caused by accumulation of the mineralization inhibitor inorganic pyrophosphate (PPi), comparably elevated levels of PPi in Phospho1−/− mice do not explain their stunted growth, spontaneous fractures, bowed long bones, osteomalacia, and scoliosis. We have previously shown that elevated PPi in Alpl−/− mice is accompanied by elevated osteopontin (OPN), another potent mineralization inhibitor, and that the amount of OPN correlates with the severity of hypophosphatasia in mice. Here we demonstrate that plasma OPN is elevated and OPN expression is upregulated in the skeleton, particularly in the vertebrae, of Phospho1−/− mice. Liquid chromatography/tandem mass spectrometry showed an increased proportion of phosphorylated OPN (p‐OPN) peptides in Phospho1−/− mice, suggesting that accumulation of p‐OPN causes the skeletal abnormalities in Phospho1−/− mice. We also show that ablation of the OPN gene, Spp1, leads to improvements in the skeletal phenotype in Phospho1−/− as they age. In particular, their scoliosis is ameliorated at 1 month of age and is completely rescued at 3 months of age. There is also improvement in the long bone defects characteristic of Phospho1−/− mice at 3 months of age. Mineralization assays comparing [Phospho1−/−; Spp1−/−], Phospho1−/−, and Spp1−/− chondrocytes display corrected mineralization by the double knockout cells. Expression of chondrocyte differentiation markers was also normalized in the [Phospho1−/−; Spp1−/−] mice. Thus, although Alpl and Phospho1 deficiencies lead to similar skeletal phenotypes and comparable changes in the expression levels of PPi and OPN, there is a clear dissociation in the hierarchical roles of these potent inhibitors of mineralization, with elevated PPi and elevated p‐OPN levels causing the respective skeletal phenotypes in Alpl−/− and Phospho1−/− mice. © 2014 American Society for Bone and Mineral Research.